[OP.8C.07] DEPLETION OF THE P22PHOX GENE REDUCED BLOOD PRESSURE RESPONSE TO GLU INJECTION INTO RVLM IN SHRSP. (September 2016) - Zahid, H.; Ferdaus, M.; Ohara, H.; Isomura, M.; Nabika, T.
Abstract : Objective: Oxidative stress in the rostral ventrolateral medulla (RVLM), a sympathetic center in brainstem, was implicated in the regulation of sympathetic activity in various hypertensive models including SHRSP. To elucidate pathophysiological roles of oxidative stress in SHRSP, we constructed a new congenic strain (referred to as SP.MES) by introducing a mutated P22phox gene of the Matsumoto Eosinophilic Shinshu (MES) rat into SHRSP. Design and method: The null mutation of P22phox in the MES rat was introduced in SHRSP by the speed congenial method. An established congenial strain called SP.MES harbored a 1.4-Mbp chromosomal fragment including P22phox on the genetic background of SHRSP. Microinjection of glutamate (Glu) and other substances was performed using that stereotaxic method, and changes in blood pressure (BP) was monitored with an intraarterial cannulated probe. Oxidative stress in the brainstem was measured with the lucigenin method. BP changes under cold stress at 4 °C was monitored with the telemetry system. Results: The level of oxidative stress was significantly reduced in the brainstem of SP.MES. Baseline BP was significantly reduce as well in SP.MES than in SHRSP (188 ± 13 vs. 220 ± 13 mmHg). Further, the BP response to Glu microinjection into RVLM was significantly lower in SP.MES than in SHRSP (24 ± 4 vs. 42 ± 6 mmHg). Tempol and losartan reduced the response to Glu significantly in SHRSP, while these reagents failed to reduce it in SP.MES. BP response to cold stress was blunted in SP.MES when compared with SHRSP. Conclusions: As P22PHOX is an essential subunit of the NADPH oxidases (NOX), these results implied that oxidative stress due to the NOX activation in the brain potentiated BP response to Glu in SHRSP, which might contribute to exaggerated response to stress as well as high baseline BP in this strain. Angiotensin II receptor type I seems to be involved in the activation of NOX.